The reality of activating Crisis Management in distance education from the point of view of school principals on the primary stage schools of the Sahab Brigade Directorate - Abu Hammad, Sawsan Ali Mohammad (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the reality of applying the thought of crisis management from the point of view of school principals on the primary stage schools of the Sahab Brigade Directorate, and in order to achieve the study target the descriptive analytical method was used by applying a questionnaire consisting of 30 items on a sample of 32 principals of primary stage schools.The study concluded that there is a medium degree of application of crisis management thought in the distance education process from the point of view of principals of primary stage schools with an average of (2.46 out 5), beside that the obstacles and difficulties of crisis management from the point of view of principals of primary stage schools comes with a medium degree with an average of (2.76), and the importance of applying the crisis management thought in distance education from the point of view of principals of primary stage schools comes with a medium degree (2.46). So, the researcher recommended making an electronic scale developed to measure the level of application of crisis management mechanisms and procedures and encourage them, and conducting remote training courses for leaders and work teams in educational institutions for training in crisis management and preparing unified guides that are circulated to help in Implementing crisis management strategies and procedures in educational institutions and continuing to implement continuous opinion polls on the obstacles and difficulties facing crisis management in order to work on overcoming them.
Keywords: Crisis management; distance education